Taxonomic study of the leafhopper genus Tautoneura Anufriev with four new species and one new record, and one new species for Qadria Mahmood (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China - Lin, Shuanghu; Zou, Hongfen; Zhang, Yalin (Zootaxa, 2024)
The genus Tautoneura Anufriev is reviewed with four new species and one new record from China: T. apicidentata, T. bicruris, T. bracteiformis, T. gigaerythromacula spp. nov. and T. indefinita (Dworakowska, 1970) n. rec. In addition, Qadria longibinata sp. nov., externally resembling members of above genus is also reported in this study. Detailed morphological descriptions and illustrations of these five new species and a key to all known species (males) of Tautoneura Anufriev from China are provided.